Population Fluctuation and Damage Caused by Phytophagous Mites on Three Rubber Tree Clones - Castro, E. B. [UNESP]; Nuvoloni, F. M. [UNESP]; Mattos, C. R R; Feres, R. J F [UNESP] (Springer Nature, 2013)
Our aim was to investigate the population fluctuation and the damage caused by the phytophagous mites Calacarus heveae Feres, Tenuipalpus heveae Baker, and Eutetranychus banksi (McGregor) on clones FX 2784, FX 3864, and MDF 180 in rubber tree crops from southeastern Bahia, Brazil. Moreover, we tested for the influence of climatic variables on occurrence patterns of these species throughout weekly samples performed from October to April. The infestation peaks was between mid-January and late February. The clones FX 2784 and FX 3864 had the highest infestations and more severe damage possibly caused by C. heveae, which was the most frequent and abundant species in all clones. We found that sunlight duration and rainfall were the most important factors for C. heveae while T. heveae was affected by rainfall and temperature. Eutetranychus banksi was only affected by sunlight duration. However, the best models had low goodness of fit. We concluded that the clones FX 2784 and FX 3864 had a higher susceptibility to mite attack, and the association between climatic variables and favorable physiological conditions were determinant for the population increase of the species from January to April. © 2012 Sociedade Entomológica do Brasil.
Keywords: Climatic factors; Hevea brasiliensis; mite management; monitoring; plant resistance; Acari; Calacarus heveae; Eutetranychus banksi; Tenuipalpus